The Effectiveness of Snowball throwing technique in teaching Grammar at Eighth Grade Students in SMP N 1 Gandrungmangu - Riza Afifah; Khairunnisa Dwinalida (Journal of Applied Linguistics (ALTICS), 2020)
According to curriculum 2013 at eighth grade junior high school level, English learners are able to speak English and use grammar in the conversation. However, there were some students’ difficulties in mastering grammar at eighth grade students of SM N 1 Gandrungmangu because of monotonous activity and limited time to study. Snowball throwing technique was proposed as a strategy to teach grammar. The goal of this study is to find out whether or not there is a significant effect of snowball throwing technique in teaching grammar at eighth grade students in SMPN 1 Gandrungmangu. This study used quasi-experiment and quantitative approach. The population of this study was the eighth grade students in SMPN 1 Gandrungmangu in academic year 2021/2022 which consists of 255 students. The sample was selected by purposive sampling with VIII G as experiment class and VIII H as control class. IBM SPSS V25 for windows was used to help analyze the data in this research. This study used pre-test and post-test with multiple choice to collect data. The result of independent sample t-test showed that there was improvement in learning achievement of the students who were taught using snowball throwing technique and it can be assumed that snowball throwing technique was used in teaching grammar is effective. Keywords : Snowball Throwing Technique, Teaching Grammar.